Sport und Sportgroßveranstaltungen in Europa - zwischen Zentralstaat und Regionen - Büch, Martin-Peter; Maennig, Wolfgang; Schulke, Hans-Jürgen (Edition HWWI, 2012)
The autonomy of sport which is constitutionally recognised is not consistently respected by EU law. There are complaints that the necessary cooperation of the federations in sport is not sufficiently taken into account. This is where the speakers of the 9th International Hamburg Symposium "Sport and Economics" come in when they address legal and economic questions about major sporting events and discuss proposals on the status of sport in the European context. It shows that sport is economically shaped, which has not yet found an adequate equivalent at European level. This is evident, for example, in sports betting and the gambling monopoly.The volume will further stimulate the debate created by the EU White Paper on Sport and the Bundestag resolution on sport in Europe.